'If we want, they help us in any way': how 'unaccompanied refugee minors' experience mentoring relationships. Issue 2 (4th March 2021) - Raithelhuber, Eberhard
ABSTRACT: Little is known about the growing phenomenon of 'mentorship for "unaccompanied refugee minors"'. This article looks into one serious gap, based on a case study in Austria, asking: How do these young people, most of them seeking asylum, represent relationships in a mentorship programme? Here, youth mentoring is understood as a community-based form of social intervention carried out by an organisation that connects trained adult volunteers with young people. The findings from two multilingual group interviews focus on various dimensions of social support and social capital, e.g. with regard to settling in and life course transitions. Reacting to calls for methodological reflection in studies on the refugee experience, the article presents in detail the setting and approach, which partly built on the concept of the 'tripled Otherness of "unaccompanied minors"'. An analysis of their narrations is discussed against the wider context, particularly that of systematic discrimination by welfare agencies and efforts by various actors to rearrange URMs' differential inclusion. The conclusion proposes that research should better reflect the political dimension in mentoring for marginalised populations. It argues that the potential of such programmes should be tapped to develop progressive protection arrangements extending beyond the limits of the welfarist nation state.